EKSEKUSI BARANG BUKTI TINDAK PIDANA NARKOTIKA YANG DIRAMPAS UNTUK NEGARA (Studi Putusan Hakim Pengadilan Negeri Balige) - Eduward Eduward; Mahmud Mulyadi; Madiasa Ablisar; Hasim Purba (USU LAW JOURNAL, 2016)
ABSTRACT Law of Criminal Procedure ( Criminal Procedure Code ) determines that the confiscated items that are restricted or prohibited for circulation, seized for use for the benefit of the country or to be destroyed. Formulation of the problem by Judge Law Enforcement Against Narcotics Crime Evidence in Decision District Court Judge  of  Balige. Narcotics Precursor and tools or goods used in the crime of Narcotics or relating to narcotics and results in stripped to the State does not have the legal certainty. Execution of Narcotics evidence was carried out by the State Attorney Balige has not been effective (based on juridical and non juridical constraints) . Keywords ; Execution evidence, narcotics, seized state